Effect of different proportions of goat milk and cow’s milk on the physical and sensory characteristics of “dulce de leche” - Chacón Villalobos, Alejandro (2013)
The objective of this work was to determine the effect of the proportion of cow and goat milk in the composition of milk candy “dulce de leche”. The evaluation was conducted at the Universidad de Costa Rica and the Instituto Nacional de Aprendizaje (from January 2010 to May 2011), to establish the effect on the pH, Brix degrees, color and texture in days 1 and 60 of storage, of different goat milk proportions in the milk candy (0%, 25%, 50%, 75% and 100%). Sensorial acceptance of such formulations was estimated for 100 consumers using formulations at day fifteen and a commercial product used as reference; this data was assessed using a cluster analysis. For all variables there is a significant effect of storage (p≤0.05), but only interactions between storage and pH were revealed. The higher the proportion of goat milk, the lower the pH, especially as storage time increases. High Brix values were needed to obtain a desirable consistency in formulations containing goat milk. The color showed significant differences (p≤0.05) but with slight variations, reddish and yellowish color being increased with time and with the percentage of substitution. Significant differences (p≤0.05) in elasticity, hardness, consistency, viscosity index and adhesiveness for all the percentage of goat milk except for 25% and 50% existed; the 0% formulation generated the greater hardness, adhesiveness and elasticity. Analysis of sensory data obtained a first cluster (63%) of people who showed a good acceptance for all samples, while a second cluster (37%) reported increased liking for the commercial brand used as reference and for the 50% substitution as well.